Group Medical Visits and Clinician Wellbeing - Ariana Thompson-Lastad PhD; Paula Gardiner MD (SAGE Publishing, 2020)
There is strong evidence for clinical benefits of group medical visits (GMVs) (also known as shared medical appointments) for prenatal care, diabetes, chronic pain, and a wide range of other conditions. GMVs can increase access to integrative care while providing additional benefits including increased clinician-patient contact time, cost savings, and support with prevention and self-management of chronic conditions. During the COVID-19 pandemic, many clinical sites are experimenting with new models of care delivery including virtual GMVs using telehealth. Little research has focused on which clinicians offer this type of care, how the GMV approach affects the ways they practice, and their job satisfaction. Workplace-based interventions have been shown to decrease burnout in individual physicians. We argue that more research is needed to understand if GMVs should be considered among these workplace-based interventions, given their potential benefits to clinician wellbeing. GMVs can benefit clinician wellbeing in multiple ways, including: (1) Extended time with patients; (2) Increased ability to provide team-based care; (3) Understanding patients' social context and addressing social determinants of health. GMVs can be implemented in a variety of settings in many different ways depending on institutional context, patient needs and clinician preferences. We suggest that GMV programs with adequate institutional support may be beneficial for preventing burnout and improving retention among clinicians and health care teams more broadly, including in integrative health care. Just as group support benefits patients struggling with loneliness and social isolation, GMVs can help address these and other concerns in overwhelmed clinicians.